Factors Influencing Residency Program Selection by Medical Students Pursuing Obstetrics and Gynecology - Alston, Meredith J. (J Grad Med Educ, 2017)
BACKGROUND : Little is known about the factors that influence medical student selection of obstetrics and gynecology (ob-gyn) residency programs. OBJECTIVE : We assessed the factors influencing residency program selection by fourth-year medical students pursuing ob-gyn training. METHODS : A voluntary, anonymous, 19-question survey of residency selection factors was distributed to all fourth-year medical students interviewing at 1 of 5 academic ob-gyn departments for a residency position during the 2013–2014 interview season. Participants were surveyed about the relative importance (not important, somewhat important, important) of various residency selection factors, including operative experience, exposure to subspecialties, curricular experience, access to fellowships, and administrative aspects of residency, including adherence to duty hour restrictions. RESULTS : Of 322 potential respondents, 262 (81%) completed the survey. Surgical training and training in laparoscopic surgery were deemed “important” by nearly all respondents (98%, 258 of 262, and 97%, 253 of 262, respectively). Factors that were considered “not important” by a significant group of respondents included maternity/paternity leave policies (22%, 58 of 259); opportunity for international rotations/electives (20%, 51 of 259); exposure to quality and safety initiatives (13%, 34 of 259); and training in abortion (13%, 34 of 262). CONCLUSIONS : Fourth-year medical students identified surgical training as the most important factor in selecting an ob-gyn residency, a finding that is particularly relevant as decreasing and changing surgical volumes affect residency training in this specialty.